Pengaruh Penjualan Kredit, Biaya Pengumpulan Piutang dan Diskon Penjualan terhadap Volume Penjualan Sepatu Cibaduyut Bandung - Nelsi Wisna (Jurnal Akuntansi, 2008)
The purpose of this research is to know and analyze the influence of sales credit/sales on account, collection cost receivable and sales discounts to sale volume. By using the purposive method, this research surveyed at 30 midle and small entrepreneur in Cibaduyut Bandung Town. Data analysis to test the hypothesis is path analysis. The result of this research shows that only credit sales having an effect on positive and significant to sale volume, while the collection cost receivable and sales discount not havean effect.Keywords :Sales credit, collection cost, sales discount, sale volume